난소기형종을 동반한 항 NMDA 수용체 뇌염 환자 1례에 대한 한방치료 증례 보고 - 남이랑; 김민화; 김마리아; 구기범; 이세연; 김소연; 박소정; 최준용; 한창우; 홍진우; 강지원; 이인; et al. (대한한방내과학회지, 2023)
Objectives: This study reports on the improvement of anti-N-methyl-D-aspartate (NMDA) receptor encephalitis with ovarian teratoma after Korean medicine treatment. Methods: A patient was treated with Korean medicine treatments, such as acupuncture and herbal medications (Gami-ondam-tang and Samulanshin-tang-gamibang). The patient's improvement was evaluated using manual muscle testing (MMT), the Mini-Mental State Exam-Korea (MMSE-K), the modified Barthel index (MBI), and the Clinical Assessment Scale in Autoimmune Encephalitis (CASE). Results: After using Korean medicine treatments, the patient's MMT, MMSE-K, and MBI scores increased, and the CASE score decreased. Conclusion: This case suggests that Korean medicine can be effective in treating the symptoms of anti-NMDA receptor encephalitis.